Cultural value and urban governance: A place for Melbourne’s music community at the policymaking table - Martin, Declan (Perfect Beat, 2017)
A city of diverse use and function is predicated on informed urban policymaking that can equitably negotiate competing economic and cultural uses of urban space. I investigate such urban policymaking in relation to liquor licensing and its mediating effect between venue-based live music and amenable residential and business districts in Melbourne, Australia. Firstly, I explore the positive externalities that flow from the operations of urban music venues, specifically the Tote Hotel and its integral place in Melbourne’s music community. Secondly, I examine how such value can be integrated with policymaking spheres that are typically dominated by economic considerations, analysing a specific instance of participatory urban governance that developed around liquor licensing in Melbourne. I conclude by evaluating the role of political agendas in achieving favourable cultural policy outcomes, inferring that cultural organizations with less political and economic relevance may be excluded from the policymaking process and, thus, the shaping of urban space.